Unraveling Phenomenological Misconceptions and Magnetism (Global Journal of Science Frontier Research, 2026)
A phenomenologically correct formulation of the problem is more than half the solution, since the resulting solution provides a rigorous description of the observed effects in the first approximation. Meanwhile, many modern theories describe basic effects using crude multiparameter models with corrections for the Landau smallness parameter. This is most clearly demonstrated in the purely relativistic effect of magnetism, which, it was assumed, is determined by a linear dependence on the charge velocity and, as a result, the description of which contains many phenomenological errors. This led not to an UNDERSTANDING of magnetism, but only to its formal mathematization, carried out in a non-rigorous manner. This led to the mathematical Physicists, without a proper analysis of the classical description of magnetism, “concluded” its quantum nature. Thus, by formally using Euler’s equations without a proper physical analysis, magnetism was incorporated into Maxwell’s equations. The resulting errors in its description were extended into both the Theory of Relativity and Quantum Mechanics itself.
Keywords: contradictions and gaps in Particular Phenomenologies; Imagination and Reality.; Orthogonal Forces